Answer:
[tex]e^{3t}(2t+5t^{2})[/tex]
Step-by-step explanation:
[tex]L^{-1}[\frac{2s+4}{(s-3)^{3}} ]=[/tex]
Using the Translation theorem to transform the s-3 to s, that means multiplying by and change s to s+3
Translation theorem:[tex]L^{1} [F(s-a)=L^{-1}[F(s)|_{s \to s-a}\\ L^{1} [F(s-a)=e^{at} f(t)[/tex]
[tex]L^{-1}[\frac{2s+4}{(s-3)^{3}} ]=e^{3t} L^{-1}[\frac{2(s+3)+4}{s^{3}} ][/tex]
Separate the fraction in a sum:
[tex]e^{3t} L^{-1}[\frac{2s+10}{s^{3}} ]=e^{3t} L^{-1}[\frac{2s}{s^{3}}+\frac{10}{s^{3}} ]=e^{3t} (L^{-1}[\frac{2}{s^{2}}]+ L^{-1}[\frac{10}{s^{3}}])[/tex]
The formula for this is:
[tex]L^{-1}[\frac{n!}{s^{n+1}} ]=t^{n}[/tex]
Modify the expression to match the formula.
[tex]e^{3t} (2L^{-1}[\frac{1}{s^{1+1}}]+ \frac{10}{2} L^{-1}[\frac{2}{s^{2+1}}])=e^{3t} (2L^{-1}[\frac{1}{s^{1+1}}]+ 5 L^{-1}[\frac{2}{s^{2+1}}])[/tex]
Solve
[tex]e^{3t} (2L^{-1}[\frac{1}{s^{1+1}}]+ 5 L^{-1}[\frac{2}{s^{2+1}}])=e^{3t}(2t+5t^{2} )[/tex]